Rehabilitating criminal justice: innovations in policing, adjudication, and sentencing - Slobogin, Christopher (Cambridge University Press, 2025)
"Every aspect of the US criminal legal system, from policing to sentencing, is in disarray. This book proffers a reform agenda that reduces the harms of policing without handcuffing law enforcement, ensures conviction of the guilty while protecting the innocent, and slashes prison populations without undermining public safety"--